IT logistics support life cycle of products in air engine - Кулик, М.С.; Тамаргазін, О.А.; Ліннік, І.І. (Proceedings of National Aviation University (archive), 2009)
Questions of increase of efficiency of a supply with information of creation and support in operation of modern aviation engines are considered. The revealed most perspective directions of development of complex systems of support of life cycle aviation technics.